Performance Analysis and Future Trends of the Mazda Wankel Rotary Engine - Wu Jianhua (E3S Web of Conferences)
As the global focus shifts towards environmental protection and sustainable energy development, electric vehicles are increasingly seen as the future of transportation. However, internal combustion engines (ICEs) continue to offer various irreplaceable advantages, particularly in terms of cost-effectiveness and reliability. The Mazda Wankel rotary engine, in spite of a lower compression ratio compared to traditional reciprocating engines, stands out for its compact size, lightweight design, and ability to deliver high horsepower with rapid operation. This unique combination of features makes the Wankel engine a noteworthy alternative to conventional ICEs. This paper will delve into the performance characteristics of the Mazda Wankel rotary engine, highlighting its strengths and limitations. Additionally, the study will explore the potential future trends for this engine technology, considering ongoing advancements and market demands. The analysis aims to provide a comprehensive understanding of the Wankel engine’s role in the automotive industry amidst the growing prominence of electric vehicles.